Brown Bear Population Management in Romania: Pilot Project Using the Benefits of Technology - Ana Gabriela ANUTOIU; Dragos DANTIS (Communications of International Proceedings, 2021)
Brown bear has accompanied the history of humanity for centuries, being subject of stories, legends, local national folklore or even becoming a symbol, enforced with special characteristics and attributes. The evolution of brown bear population has been marked by asymmetry, in some regions being hunted extensively, while in other ones has been included on the list of protected species and benefiting from increase in the number of individuals. One of the countries where the growth of the brown bear population has been seen is Romania, leading in some cases to events in the local communities, accompanied by life or material losses. These unfortunate happenings conducted to public debates regarding the interaction between the communities and the bear population and forced the authorities to search and consider possible solutions. One of these will be described in the current paper, providing the example of a pilot project to be rolled out, where the technology will be used to register, monitor and protect the wildlife.
Keywords: Brown Bear; Local Community; Technology; Sanctuary